Effect of dietary L-carnitine on finishing pig growth performance, meat quality, and stress parameters during handling - James, Bradley William (Kansas State University, 2009)
Four experiments were conducted to determine the interactive effects of dietary L-carnitine and ractopamine HCl (ractopamine) on finishing pig growth performance. In analysis of treatments common to all experiments, ractopamine increased (P < 0.01) ADG and G:F compared to pigs not fed ractopamine. Added L-carnitine tended to increase (P < 0.07) ADG and improved (P < 0.01) G:F compared to pigs not fed L-carnitine. Three experiments were conducted to determine the effects of L-carnitine and ractopamine on carcass characteristics and meat quality. In Exp. 1, drip loss decreased (linear, P < 0.04) in pigs fed increasing L-carnitine. In Exp. 2, drip loss decreased (P < 0.04) with increasing L-carnitine when fed with ractopamine. Percentage lean was higher (P < 0.01) for pigs fed ractopamine. In Exp. 3, lean percentage increased (P < 0.03) in pigs fed L-carnitine or ractopamine. Pigs fed L-carnitine tended (P < 0.06) to have decreased drip loss. These results suggest that ractopamine increases carcass leanness and L-carnitine reduces drip loss when fed in combination with ractopamine. Two experiments were conducted to determine the effects of L-carnitine and ractopamine on the metabolic response to handling. Non-gentle handling increased (P < 0.01) lactate and rectal temperature, and decreased pH. In Exp. 1, non-gentle handled pigs fed ractopamine had decreased (P < 0.01) pH and increased temperature and tended (P < 0.09) to have higher lactate than other pigs. In Exp. 2, lactate and temperature changes from immediately post-handling to 1 h post-handling were not different for pigs fed L-carnitine or ractopamine suggesting that L-carnitine did not decrease recovery time of pigs subjected to non-gentle handling or fed ractopamine. These results suggest that pigs fed ractopamine are more susceptible to stress when handled aggressively. Because carnitine did not alleviate the negative effects of handling for pigs fed ractopamine, the improvement in drip loss from feeding carnitine must be due to a different mode of action.
Keywords: Pigs; L-carnitine; Ractopamine HCl; Handling; Stress; Phosphorus; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473)